PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK PENGUASAAN KETERAMPILAN PRAKTEK PEMERIKSAAN KEHAMILAN - Jumiarti, Ratna; Marmawi, Marmawi; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to(1) design an interactive multimedia of midwifery subjectsfor prenatal care practice skills (2) present an interactive multimedia display of midwifery courses for pregnancy practice skills (3) to discribe the acquisition of student learning outcomes in pregnancy practice skills.this research is a product development research that produces interactive multimedia learning CD for mastery pregnancy practice skills. The results of the research are : (1) Multimedia development begins by arranging prescriptions of learning tasks, designing storyboards and followed by depelopment of multimedia learning validated by experts for ensure the quality of multimedia produced. The results show that multimedia is suitable for use as a medium of learning. (2) Multimedia that has been developed is verry appropriate used in conveying practice material of pregnancy examination. (3) Acquisition of learning results obtained showed that students are able to conduct the process of pregnancy examination with a series. It can be concluded that the development of interactive multimedia for the mastery of practical skills of pregnancy examination is very helpful for lecturers and students in the learning process independently.Keywords: Development, interactive, skill practice antenatal care.